2022
DOI: 10.3389/fimmu.2022.972746
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and immunological characteristics of five patients with immune dysregulation, polyendocrinopathy, enteropathy, X-linked syndrome in China–expanding the atypical phenotypes

Abstract: BackgroundImmune dysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome is a rare disorder of the immune regulatory system caused by forkhead box P3 (FOXP3) mutations. Abnormal numbers or functions of regulatory T (Treg) cells account for the various autoimmune symptoms. We aimed to explore the molecular genetics and phenotypic spectra of patients with atypical IPEX syndrome in China.MethodsWe analyzed the molecular, clinical and immune phenotype characteristics of five Chinese patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
(48 reference statements)
0
2
2
Order By: Relevance
“…Consistent with these normal levels of IL‐17, the frequency of Th17 cells was not elevated in most of the patients, the exception being a few with typical and early onset IPEX. Recently, variability in Th17 cell frequencies has been shown in a group of three IPEX patients 34 . These data tend to contrast our own findings, as well as those of other groups 26,31,32 .…”
Section: Overview Of the Immune Landscape Of Ipex On A Cellular And M...contrasting
confidence: 94%
See 1 more Smart Citation
“…Consistent with these normal levels of IL‐17, the frequency of Th17 cells was not elevated in most of the patients, the exception being a few with typical and early onset IPEX. Recently, variability in Th17 cell frequencies has been shown in a group of three IPEX patients 34 . These data tend to contrast our own findings, as well as those of other groups 26,31,32 .…”
Section: Overview Of the Immune Landscape Of Ipex On A Cellular And M...contrasting
confidence: 94%
“…Recently, variability in Th17 cell frequencies has been shown in a group of three IPEX patients. 34 These data tend to contrast our own findings, as well as those of other groups. 26,31,32 However, the following experimental evidence sheds light on these apparent discrepancies in the different patients and across the different studies.…”
Section: Overvie W Of the Immune L Andsc Ape Of Ipe X On A Cellul Ar ...contrasting
confidence: 92%
“…Luo et al reported a case of IPEX carrying the same mutation that presented with metaplastic atrophic gastritis and villus atrophy in the descending part of the duodenum ( 20 ). There have been several cases of eosinophilic esophagitis reported in IPEX syndrome ( 21 ) as well as at least two patients with pyloric stenosis described by Fang et al ( 22 ), but it is rare to see chronic gastritis with eosinophilic infiltration ( 23 ). In this report, we described an atypical IPEX case presenting with severe gastritis and pyloric stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive study of 96 patients with IPEX showed a classical triad of type 1 diabetes, eczema, and enteropathy as the most common manifestations. Apart from the classical triad, other manifestations include failure to thrive, alopecia, dermatitis, arthritis, autoimmune pancreatic exocrine insufficiency, gastritis, kidney disease, interstitial lung disease, and infection [ 25 , 26 ]. Table 3 summarizes the studies reporting infections in patients with IPEX syndrome.…”
Section: Syndromes With Autoimmunity Due To Treg Defectsmentioning
confidence: 99%